Frequency of Bleeding Duodenal Ulcer in Patients Presenting with Upper Gastrointestinal Bleeding: Frequency of Duodenal Ulcer in patients with Gastrointestinal Bleeding - Fahim, Muhammad; Sohail, Muhammad; Sajjad Khan, Muhammad; Khan, Fahim Ullah; Ur Rashid, Salman; Akhter, Shakeel (Pakistan Journal of Health Sciences, 2022)
Acute upper gastrointestinal bleeding is a well-known complication of peptic ulcers and erosions. The prevalence of Upper Gastrointestinal bleeding ranges from 48-160 patients per 100,000 people, with consistent reports of higher incidence among elderly and men. Objective: To determine the incidence of duodenal ulcer bleeding in patients admitted to the tertiary care hospital with bleeding from the upper gastrointestinal tract. Methods: The study included 270 patients, 20 to 70 years of age, of both sexes with upper gastrointestinal bleeding within 24 hours of symptom onset. A detailed interview and complete physical examination were performed. Endoscopic examination protocols were followed and accomplished within 48-hrs of the start of symptoms as bleeding. All of the above information, including age, sex and duodenal ulcer, was documented in a formerly designed proforma. The data were analyzed and entered in SPSS 22.0. Results: The mean age and SD were 54.5 + 10.54. 110 (40.74%) patients were 20-45 years old and 160 (59.25%) subjects were 46-70 years old. 190 (70.37%) patients were male and 80 (29.62%) females. While in this study duodenal ulcer was seen in 64 (23.70%) patients, 206 (76.29%) patients did not have duodenal ulcer. Conclusions: Upper Gastrointestinal bleeding is secondary to duodenal ulcers due to an increase in early readmissions over time, as observed in this local population, resulting in a higher incidence of duodenal ulcers in our local population.